PENGARUH POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN BELAJAR SISWA - Mulyawati, Yuli; Christine, Citra (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2019)
This type of research is quantitative with a causal approach consisting of independent variables (parenting parents) and dependent variables (learning independence). The purpose of this study is to describe the effect of parenting on the independence of student learning. Collecting research data using a five-scale questionnaire instrument. To find the magnitude of the effect of parenting parents using the statistical calculation model Carl Person Corelation Product Moment. For reliability calculated using the Cronbach Alpha formula. A sample of 49 students was obtained using the Taro Yamane formula. Analysis prerequisite testers are Liliefors normality test. After the normality test, the homogeneity test is done by Fisher's test. Instruments that are valid and reliable are used to collect data on the results that show there is an influence of parenting parents on student learning independence. Simple regression analysis and correlation techniques produce a model of influence expressed in the form of a regression equation that is Y ̌ = (87.22+ 0.06X), with the F value of 0.281 greater than F table with a level of 0.05 of 4.06 and its contribution is 49%. The conclusion of the study is that there is a positive effect of parenting on the learning independence of students in fifth grade of Cibubur Public Elementary School 03 Odd Semester Cibubur 03 in the odd semester of the 2018/2019 academic year.